2016
DOI: 10.1177/0271678x16662043
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasomes link vascular disease with neuroinflammation and brain disorders

Abstract: The role of inflammation in neurological disorders is increasingly recognised. Inflammatory processes are associated with the aetiology and clinical progression of migraine, psychiatric conditions, epilepsy, cerebrovascular diseases, dementia and neurodegeneration, such as seen in Alzheimer's or Parkinson's disease. Both central and systemic inflammatory actions have been linked with the development of brain diseases, suggesting that complex neuro-immune interactions could contribute to pathological changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(82 citation statements)
references
References 224 publications
(290 reference statements)
1
78
0
3
Order By: Relevance
“…36 In addition, neurodegenerative disease and dementia may also be associated with activated systemic inflammation in diabetes mellitus, hyperlipidemia, atherosclerosis, hypertension, obesity, metabolic syndrome and infection, presumably by inducing vascular changes and activation of microglia cells in the brain. 7 …”
Section: Introductionmentioning
confidence: 99%
“…36 In addition, neurodegenerative disease and dementia may also be associated with activated systemic inflammation in diabetes mellitus, hyperlipidemia, atherosclerosis, hypertension, obesity, metabolic syndrome and infection, presumably by inducing vascular changes and activation of microglia cells in the brain. 7 …”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, the BBB is not only a passive part of the neuroinflammatory processes. Besides immune cells and resident cells with well-characterized immune functions, cellular components of the BBB like CECs and brain vascular pericytes can be involved in inflammatory responses (Lénárt et al, 2016;Navarro et al, 2016a). In these cells innate immune mechanisms are launched during the initial phase of neuroinflammation.…”
Section: Role Of the Bbb In Neuroinflammationmentioning
confidence: 99%
“…Increasing evidence suggests that besides immune cells, cells of the NVU can also express and activate PRRs and inflammasomes. Recent research has revealed that astrocytes and neurons express several TLRs (Lee et al, 2013) and NLRs, and they are able to activate inflammasomes in various neurological diseases (Lénárt et al, 2016). However, there is only few data about the expression and activity of PRRs and inflammasomes in CECs and brain pericytes and their role in neuroinflammation.…”
Section: Prrs In the Cells Of The Bbbmentioning
confidence: 99%
See 2 more Smart Citations